ADOPSI INOVASI MEDIA KOMUNIKASI PEMASARAN UMKM BATIK JUMPUTAN DI ERA DIGITALISASI - Riski Damastuti (Universitas Teuku Umar, 2020)
Marketing communication media develops as technology develops. Adaptation and adoption of digital marketing communication media is a challenge for the kelompok UMKM batik jumputan Tahunan Yogyakarta. Tthe purpose of this study is to find out how the process of adoption of digital marketing communication media in kelompok UMKM batik jumputan Tahunan, Yogyakarta. The method used in this research is descriptive qualitative. The data in this study were obtained through in-depth interviews with parties related to kelompok UMKM batik jumputan Tahunan, Yogyakarta, as well as direct or indirect observations of the digital marketing communication process carried out. The results of this study, it is known that the adoption of digital marketing communication media by kelompok UMKM batik jumputan Tahunan, Yogyakarta are still very low.Keywords: UMKM, adoption of innovation, marketing communication